Monetary Policy and Risk-Premium Shocks in Hungary : Results from a Large Bayesian VAR - Popescu, Adina (IMF Working Papers; Working Paper, 2011)
We document the transmission of monetary policy and risk-premium shocks in Hungary, by applying recent advances in the Bayesian estimation of large VAR models. The method allows extracting information from over 100 series, opening the "black box" of the transmission mechanism to provide the most comprehensive description to date of the impact of these two shocks on the economy under the inflation-targeting regime. We find novel evidence that most of the channels of transmission are operational in Hungary, in spite of large liability euroization and high foreign ownership of banks and corporations. Due to financial stability concerns, monetary policy responds procyclically to risk-premium shocks. We also find that the use of such a large panel of data improves inflation forecasting performance over smaller models and renders this model suitable for policy purposes.